Refuting evolution a handbook for students, parents and teachers cuntering the latest arguments for evoltion - Sarfati, Jonathan, 1964- (Acacia Ridge, QLD Answers in Genesis, 1999)
Includes bibliographical references and index.
Keywords: Evolution -- controversial literature; Creation science versus evolution